‘We don’t know nearly enough’: an online survey exploring perspectives of specialists who support children with brain-based visual impairments - Jakubowski, Josephine Sabrina; May, Eloise; Findlay, Rebecca; McDowell, Nicola; Simkin, Samantha K.; Hamm, Lisa M. (Frontiers in Human Neuroscience, 2025)
IntroductionChildren with brain-based visual impairments (some of whom have a diagnosis of Cerebral Visual Impairment, or ‘CVI’) represent a growing and underserved population within vision services. These children often have more complex needs than those with ocular visual impairments and benefit from specialist support from multiple disciplines. This study aimed to understand the perspectives of these specialists in terms of their goals, views on collaboration, and understanding of the term ‘CVI’.MethodsWe invited a range of specialists who work with children with brain-based visual impairments, including educators, rehabilitation staff, clinicians, and family members, to complete an online survey between April 2023 and April 2024.ResultsThe analysis included 94 respondents: 51 educators, 30 rehabilitation staff, 7 clinicians, and 6 family members. Respondents shared common goals of connecting with the child (87/94, 93%) and fostering their learning and development (82/94, 93%). However, respondents also noted some specific and divergent goals, which can be at odds with each other. Professional staff frequently identified family members as the most valuable source of information about their child’s vision (36/88, 41%), though family members expressed feeling under-valued. Transdisciplinary clinics were highlighted as a helpful model to provide quality child-centered care. Of the 73 professional staff who reported being familiar with the term ‘CVI’ (73/88, 83%), most (61/73, 84%) thought it was underdiagnosed, but respondents had different perspectives on what a diagnosis meant. Only 73% of professionals familiar with CVI reported receiving formal training about it.DiscussionThe varied goals and different perspectives on CVI create challenges to providing cohesive support for children with brain-based visual impairments. Increasing the availability of complementary formal training across disciplines and adopting transdisciplinary models of care are promising approaches to improve the quality of services.